Socialization of the P5-PPRA learning program for Aisyiyah early childhood education teachers, Gatak District - Lestari, Sri; Widyasari, Choiriyah; Fitriyah, Qonitah Faizatul; Kartikasari, Sri Wahyuni; Hertinjung, Wisnu Sri; Andrianie, Prilya Shanty; Handayani, Arifah; A'yyun, Aisyah Qurrota; Ar Rasyid, Yazid Fadhil; Qaidatiningsih, Salmarani Putri; Nafisah, Shafa Oktavia; Nisa, Asiyah Khoirun; Yudiningrum, Firdastin Ruthnia (Universitas Muhammadiyah Magelang, 2025)
The Project for Strengthening Pancasila Student Profile and Rahmatan Lil Alamin Student Profile (P5-PPRA) learning program has been declared a mandatory program within the Merdeka Curriculum. However, teachers at Aisyiyah Early Childhood Education (PAUD) in Gatak District lack adequate understanding of it. The objective of this community service activity was to enhance Aisyiyah PAUD teachers' understanding of the P5-PPRA learning program. The methods used included lectures, question-and-answer sessions, and discussions. After participating in the socialization, participants' knowledge and understanding of the concepts, principles, and benefits of P5-PPRA increased from 58.13% to 90.69%. This improved understanding equips Aisyiyah PAUD teachers with sufficient preparation to implement the P5-PPRA learning program in the classroom. Mastery of the P5-PPRA learning program is expected to improve the quality of Aisyiyah PAUD education.